Incidence and outcome of neonatal seizures at a tertiary care hospital - Abdul Bari, Abdul Naseer; Pathan, Habib G.; Kokiwar, Prashant R. (International Journal of Contemporary Pediatrics, 2017)
Background: Seizures are associated with poor neuro developmental outcome if not diagnosed early and treated properly. During newborn period, seizures indicate underlying neurological disease. Neonatal seizures lead to increased morbidity and mortality usually found in neonatal intensive care unit. The objective of this study was to evaluate incidence and outcome of neonatal seizures. Methods: Present study was hospital based prospective study conducted among 117 neonates of 0-28 days of age at a tertiary care hospital for a period of one year. The data like history, clinical examination and investigation findings was recorded in the pre-designed, pre-tested, semi structured questionnaire. Results: The incidence of neonatal seizures was higher in male neonates. Subtle types of seizures were the commonest type of seizures. In term neonates, the birth asphyxia was the most common cause of neonatal seizures. The incidence of intra-ventricular hemorrhage (IVH) was significantly higher in preterm than term neonates. Out of biochemical abnormalities, the hypocalcemia was the most common cause of the neonatal seizures. Common causes of neonatal deaths in our center were severe birth asphyxia, intra-ventricular hemorrhage (IVH), septicemia and meningitis. Conclusions: Most of the causes of neonatal seizures are preventable by good perinatal care and early interventions while metabolic seizures need a sharp vigilance and early suspicion.